One Earth, Four or Five Words. The Peripheral Concept of “Avant-Garde” - Bäckström, Per (Nordlit, 2007)
Metaphors grow old, turn into dead metaphors, and finally become clichés. This succession seems to be inevitable - but on the other hand, poets have the power to return old clichés into words with a precise meaning. Accordingly, academic writers, too, need to carry out a similar operation with notions that are worn out by frequent use in everyday language. One metaphor that has been hollowed out in such a way, through lax use by journalists and literary historians, is the concept of "avant-garde". In this article, I shall try to shed some new light upon this notion, with the purpose of showing its different national use and heterogeneity of meaning. This pluralism is overlooked today because of the hegemony of English in academic studies, which leads one to believe that a consensus exists in the use of the term "avant-garde", since so many academics write their articles and books in this language. The current analysis is directed towards theoreticians’ ways of dealing with the notion in question, by which I meaneverybody who writes or thinks about the notion of "avant-garde". This article is an attempt to recuperate the term to stringent use and gain a deeper insight into the aesthetic movements of modernity and late modernity. I hope to show that, despite the fact that many writers believe that there exists only one recognition of the notion of "avant-garde", the understanding of the Anglo-American "centre" is actually as peripheral as that of other countries - which are normally regarded as peripheries.